Travelling wave and non-travelling wave solutions of nonlinear evolution equation via new generalized and Improved (G'/G) - expansion method - Khan, Anika Tahsin (BRAC Univeristy, 2018)
This thesis is submitted in a partial fulfilment of the requirements for the degree of Bachelor of Science in Mathematics 2018.